Building public trust in cooperatives through digitalization - Indriastuti, Dorothea Ririn; Susanti, Rina; Wulandari, Rina; Intan, Juliana (Journal of Management and Digital Business, 2025)
The Digital Economy is the implementation of computers and communication technology through the Internet to facilitate business processes. The digital economy allows many activities that previously had to be done offline to be converted online through the help of information technology. The economic sector in Indonesia that is affected by digitalization is cooperatives. Cooperatives are business entities known as pro-people and have legal entities in Indonesia. This explanatory research study aims to test and explain the causal relationship between research variables through hypothesis testing. The approach taken in this study is a quantitative research approach. This research focuses on discussing the factors that improve the welfare of cooperative members, namely digitalization and trust. In this study, the researcher used 214 respondents who were members of savings and loan cooperatives in the Greater area of Surakarta. This study uses structural equation modeling (SEM) to test the hypothesis. The results of this study show that digitalization and trust can affect the welfare of cooperative members. In addition, trust can mediate the relationship between digitalization and the welfare of cooperative members.